2014
DOI: 10.1108/er-02-2013-0025
|View full text |Cite
|
Sign up to set email alerts
|

The impact of best HRM practices on performance – identifying enabling factors

Abstract: Purpose – The purpose of this paper is to empirically examine the relationships between best human resource management (HRM) practices, knowledge management (KM), organization learning and organizational capabilities (OC), as well as their impact on organizational performance. Design/methodology/approach – To carry out this research, a structured questionnaire was designed and distributed to 212 manufacturing firms which employ at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 107 publications
(114 reference statements)
2
31
0
Order By: Relevance
“…Inconsistently, Kuo (2011) found a non-significant direct relationship between HRM practices and OP. The positive association of HRM practices and KM was also asserted by Theriou and Chatzoglou (2014), Kuo (2011) and Donate and Guadamillas (2011). Furthermore, Shehata (2015), Gharakhani and Mousakhani (2012), Marqués and Simón (2011), Zack et al (2009), Mills and Smith (2011 and Kuo (2011) confirmed the significant impact of KM on OP.…”
Section: Hypotheses Testingsupporting
confidence: 52%
See 1 more Smart Citation
“…Inconsistently, Kuo (2011) found a non-significant direct relationship between HRM practices and OP. The positive association of HRM practices and KM was also asserted by Theriou and Chatzoglou (2014), Kuo (2011) and Donate and Guadamillas (2011). Furthermore, Shehata (2015), Gharakhani and Mousakhani (2012), Marqués and Simón (2011), Zack et al (2009), Mills and Smith (2011 and Kuo (2011) confirmed the significant impact of KM on OP.…”
Section: Hypotheses Testingsupporting
confidence: 52%
“…the relationship between HR practices and KM and OP, the results highlighted a positive influence of these practices on OP. Theriou and Chatzoglou (2014) examined the effect of best practices in HRM (compensation and incentives, contingent on performance, employee health and safety, employee involvement, internal communication arrangements, extensive training, harmonization, internal career opportunities, job descriptions, selective hiring, use of teams and decentralization) on KM, using a sample comprising a total of 212 HR managers operating in the Greek manufacturing industries. With respect to the relationship between HRM practices and KM, the results supported the hypothesis that best practices in HRM positively affect KM.…”
Section: Human Resource Management and Knowledge Managementmentioning
confidence: 99%
“…"Epistemology of practice" follows a duality philosophy that depends upon structurational models, theories of practice and pragmatism [15]. The most important factor here is the personal nature of tacit knowledge, which requires the willingness, on the part of those workers who possess it, to share and communicate it [16].…”
Section: Knowledge and Knowledge Managementmentioning
confidence: 99%
“…IC incorporates some behavioral characteristics required to solve basic problems related to the organization. However, knowledge base cannot progress effectively in absence of KM processes (Theriou and Chatzoglou, 2014). In complex situations, employees are required to collaborate with others to share their knowledge and expertise so that organizational problems can be solved easily (Bhatt, 2002).…”
Section: Km Process and Individual Competencementioning
confidence: 99%